AR masks in social media as a tool for assessing students’ achievements - Sembayev, Talgat; Abildinova, Gulmira; Alzhanov, Aitugan; Taibolatov, Кuandyk; Mukanova, Togzhan (International Journal of Innovative Research and Scientific Studies, 2025)
In today's educational environment, augmented reality is becoming an increasingly demanded and promising technology. Studies prove the success of its application due to the effect of implementation in the learning environment with the overlay of virtual objects that expand our three-dimensional space by visualizing and presenting interactive materials. However, its evaluative function in learning as an auxiliary tool integrated into social media is not sufficiently explored. Therefore, the purpose of this study is to determine the impact of AR masks in social media as an assessment tool on learners' academic achievement in the learning process. The research methods combined a questionnaire survey of students and teachers, the development and implementation of AR masks, and conducting a pedagogical experiment, which had a quasi-experimental format. The preliminary questionnaire survey involved 1,259 students and 76 teachers who expressed their attitudes towards the use of social media for learning purposes, prompting the consideration of methodological features in the development of 10 AR masks for social networks such as TikTok, Facebook, and Instagram. The experiment itself, where the developed AR masks were applied, involved 149 students who were divided into control and experimental groups. As a result of using AR masks, the average score of the experimental group increased from 73.8% to 79.8%. Based on the findings, it can be concluded that the use of AR masks in social media has a positive effect and significant potential to transform traditional assessment methods.